2021
DOI: 10.1093/ajcn/nqab070
|View full text |Cite
|
Sign up to set email alerts
|

Adequate protein intake in older adults in the context of frailty: cross-sectional results of the Nutrition and Health Survey in Taiwan 2014–2017

Abstract: Background Emerging evidence suggests that a dietary protein intake higher than the current recommended dietary allowance of 0.8 g/kg body weight (BW)/d may be needed to maintain optimal muscle mass, strength, and function in older adults. However, defining optimal protein intake in this age group remains a challenge. Objective In this study we sought to describe the dietary protein intake in frail, prefrail, and robust older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…The impaired micro-and macro-nutrients status, in turn, accelerates the loss of muscle mass. Adequate total protein intake (≥1.2 g/kg body weight) from food sources has been identified among the dietary determinants in frailty prevention [23]. In contrast to other studies, intake of protein-rich foods does not show relevance to frailty in our study [24,25].…”
Section: Discussioncontrasting
confidence: 89%
“…The impaired micro-and macro-nutrients status, in turn, accelerates the loss of muscle mass. Adequate total protein intake (≥1.2 g/kg body weight) from food sources has been identified among the dietary determinants in frailty prevention [23]. In contrast to other studies, intake of protein-rich foods does not show relevance to frailty in our study [24,25].…”
Section: Discussioncontrasting
confidence: 89%
“…The main characteristics of the included cross-sectional studies are shown in Table 1. Twelve cross-sectional studies [12][13][14]16,17,[23][24][25][26][27][28][29] that examined 13,593 community-dwelling older adults with a mean age of approximately 73.0 years were included. In all studies, frailty was identified according to the frailty phenotype (FP) [30].…”
Section: Main Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Figure 5. Mean and standard deviation for (a) animal-and (b) plant-based protein intake in ro and frail people[14,27,28].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
Fig. 5 Sex and age-specific level of average daily caloric intakes, Nutrition and Health Survey in Taiwan [ 189 ] (unpublished data from the author)
…”
Section: Midlife Tune Up For Women: a Critical Point For Risk Screeni...mentioning
confidence: 99%